Continuum approximation models for joint delivery systems using trucks and drones. Issue 4 (20th April 2020) - Li, Yushan; Zhang, Guangzhi; Pang, Zhibo; Li, Lefei
ABSTRACT: This research focuses on exploring the economics related to the joint delivery system using trucks and drones. Transportation distances and costs are approximated as simple functions  using continuum approximation (CA) methods, which can keep key issues and tradeoffs in focus. The main contribution is to develop cost models using the derived methods and gain a greater understanding of delivery activities by focusing on the tradeoffs between major components, which are valuable for decision-makers: choose economical delivery mode based on customer density, partition service region into  optimal  sub-regions, and obtain an optimal delivery ratio between trucks and drones.